ANALISIS KESALAHAN SISWA PADA PENYELESAIAN SOAL TRIGONOMETRI KELAS X MIPA 6 SMA NEGERI 5 PALU BERDASARKAN KEMAMPUAN MATEMATIKA: Analysis Of Student’s Errors in Solving Trigonometry Question at Palu Senior High School Based on Mathematical Skills - Kurniawan, Esa; Sugita, Gandung; Anggraini, Anggraini; Pathuddin, Pathuddin (Aksioma, 2024)
This study aims to obtain a description of students’ errors in solving trigonometry in class X Science Program 6 SMA Negeri 5 Palu based on mathematical ability. The errors in this study were divided into three according to Kastolan’s Errors theory, namely concept errors, procedural errors and technical errors. This research was conducted descriptive research with a qualitative approach. The subjects of this study were 2 students, namely 1 student with high mathematical ability and 1 student with low mathematical ability. This research was conducted in the even semester of the 2023/2024 academic year. Data were collected by means of test and interviews. Data analysis technique in this study are data condensation, data display, and drawing conclusion. The result showed that: (1) Subject with high mathematics ability did not make concept error, but made procedural error and technical error in solving trigonometry question. (2) Subject with low mathematics ability made conceptual errors and procedural errors, but did not make technical errors in solving trigonometry question.